Kemampuan Pemecahan Masalah Peserta Didik Pada Model Problem Based Learning (PBL) Kelas X SMA Negeri 3 Makassar - Amaliah, Anisatya; Wiharto, Muh; Palennari, Muhiddin (Universitas Negeri Makassar, 2020)
Abstract. This research aimed to determine the effect of Problem Based Learning (PBL) model towards student’s problem solving ability in climate change lesson of grade X students Senior High School 3 Makassar. This was a quasi- experimental research with pre-test- post test control group design and consist of two groups which were experimental group and control group. The population of this study is grade X students of Senior High School 3 Makassar and the two groups were chosen by using random sampling technique. The groups chosen as the research sample is X MIA 1 as the experimental group and X MIA 5 as the control group. Type of research instrument that used were essay test and multiple choice. Data of problem- solving ability was collected by essay test that given before and after treatment and then analyzed by using descriptive statsistics and inferential statistics. Descriptive statistic used to describe student’s problem solving ability and inferential statistics used to hypothesis test by analysis of covariance. The results shows that the significant value between PBL and student’s problem solving ability was 0,000 (α < 0,05) and the significant value between PBL and learning outcomes was 0,000 (α < 0,05). Based on the result obtained, it can be coclude that the application of PBL on learning process affect problem solving ability and Climate Change lesson of grade X students Senior High School 3Makassar.Keywords: problem-based learning (PBL), problem solving ability